PERLINDUNGAN HUKUM TERHADAP PEMENUHAN HAK NARAPIDANA LANJUT USIA DI LEMBAGA PEMASYARAKATAN KELAS IIA KUNINGAN - Hidayat, Sarip; Budiman, Haris; Yuhandra, Erga; Akhmaddhian, Suwari (IAIN Ambon, 2024)
Prisoner carry on age own condition physical and mental already No as good as prisoners who are still young, so institution correctional must give treatment special in fulfillment rights as a prisoner elderly. A phenomenon discovered by researchers at Correctional Institutions Class IIA Kuningan that is disturbed health prisoner elderly, not yet exists block special prisoner elderly, and less maximum coaching to prisoner elderly. Research methods nature descriptive-exploratory with approach juridical empirical. Results and Discussion study that arrangement protection law right prisoner carry on age in Correctional Institutions Class IIA Kuningan that is Constitution Number 22 of 2022 Article 7, article 9 and article 10 paragraphs (1,2,3 and 4) concerning Correctional that right prisoner covers worship, care or health, education and teaching (coaching), proper food, delivery complaint, follows media broadcasts, visits family , wages and allowances, remission, assimilation, liberation conditional, and leave approaching free; implementation protection to right prisoner carry on age in Correctional Institutions Class IIA Kuningan Already done but Still not enough effective, special in matter right maintenance or health as well as right education and teaching (coaching). Maintenance rights or health Not yet effective Because No exists doctor special whereas right education and teaching (coaching) not yet effective Because lack of ability prisoner in understand material presented​ in coaching . Apart from that, not yet exists block special prisoner carry on age so that the education and teaching (coaching) process is lacking walk with maximum. Keywords: protection, prisoners, continue​ age.